Whole-Genome Expression Profiling in Skin Reveals SYK As a Key Regulator of Inflammation in Experimental Epidermolysis Bullosa Acquisita - Samavedam, Unni K.; Mitschker, Nina; Kasprick, Anika; Bieber, Katja; Schmidt, Enno; Laskay, Tamás; Recke, Andreas; Goletz, S.; Vidarsson, Gestur; Schulze, Franziska S.; Armbrust, Mikko; Schulze Dieckhoff, Katharina; et al. (Frontiers in Immunology, 2018)
Because of the morbidity and limited therapeutic options of autoimmune diseases, there is a high, and thus far, unmet medical need for development of novel treatments. Pemphigoid diseases, such as epidermolysis bullosa acquisita (EBA), are prototypical autoimmune diseases that are caused by autoantibodies targeting structural proteins of the skin, leading to inflammation, mediated by myeloid cells. To identify novel treatment targets, we performed cutaneous genome-wide mRNA expression profiling in 190 outbred mice after EBA induction. Comparison of genome-wide mRNA expression profiles in diseased and healthy mice and construction of a co-expression network identified Sykb (spleen tyrosine kinase, SYK) as a major hub-gene. Aligned, pharmacological SYK inhibition protected mice from experimental EBA. Using lineage-specific SYK-deficient mice, we identified SYK expression on myeloid cells to be required to induce EBA. Within the predicted co-expression network, interactions of Sykb with several partners (e.g., Tlr13, Jdp2 and Nfkbid) were validated by curated databases. Additionally, novel gene-interaction partners of SYK were experimentally validated. Collectively, our results identify SYK expression in myeloid cells as a requirement to promote inflammation in autoantibody-driven pathologies. This should encourage exploitation of SYK and SYK-regulated genes as potential therapeutic targets for EBA and potentially other autoantibody-mediated diseases.